2021
DOI: 10.24996/ijs.2021.62.1.17
|View full text |Cite
|
Sign up to set email alerts
|

3D Facies Modeling of Mishrif Reservoir in Halfaya Oil Field

Abstract: This research deals with the study of the types and distribution of petrographic microfacies and Paleoenvironments of Mishrif Formation in Halfaya oil field, to define specific sedimentary environments. These environments were identified by microscopic examination of 35 thin sections of cutting samples for well HF-9H as well as 150 thin sections of core and cutting samples for well HF-I. Depending on log interpretation of wells HF-1, HF-316, HF-109, IIF-115, and IIF-272, the sedimentary facies were traced vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Based on [15] study, the main reservoir unit of the Mishrif Formation is MB1. [16] subdivided the Mishrif Formation in the Halfaya oil field into five teams and mentioned that the MB1 and MB2 are the most important units in the formation as main oil-bearing units due to the good reservoir properties…”
Section: Discussionmentioning
confidence: 99%
“…Based on [15] study, the main reservoir unit of the Mishrif Formation is MB1. [16] subdivided the Mishrif Formation in the Halfaya oil field into five teams and mentioned that the MB1 and MB2 are the most important units in the formation as main oil-bearing units due to the good reservoir properties…”
Section: Discussionmentioning
confidence: 99%
“…Within the Mishrif succession, microfacies study revealed the presence of six major Paleoenvironments: basin, slope, shoal, Rudist biostrome, rear shoal and lagoon (Nasser, 2021).It is the continuous deposition of shallow marine carbonates. Iraq's most prolific period contains over 80% of the country's oil reserves.…”
Section: Introductionmentioning
confidence: 99%